2008
DOI: 10.1007/s10643-008-0247-2
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Community and Peer Culture in Kindergarten

Abstract: This study reflects a naturalistic, interpretive 5-month study in a public school morning kindergarten regarding the children's social development and creation of a peer culture during the transitional months into public education. The main focus of the research was the children's perspectives on these transitions and their evolving classroom community and peer culture in response to the teacher, classroom and school environment. This study captures the dynamic and complex flow of activity that occurs in class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
0
13
0
2
Order By: Relevance
“…The members of the classroom form a classroom community by voicing their identities, expressing their individuality, and exerting agency over their environment (Lash 2008). Thus, as children work and play together, they create their own culture.…”
Section: Children's Temperament and Peer Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…The members of the classroom form a classroom community by voicing their identities, expressing their individuality, and exerting agency over their environment (Lash 2008). Thus, as children work and play together, they create their own culture.…”
Section: Children's Temperament and Peer Relationshipsmentioning
confidence: 99%
“…For example, Rudasil and Konold's (2008) findings indicated that shyer children or children with greater self-control at kindergarten entrance were rated by their teachers to be more cooperative and to have higher levels of self-control. These kinds of skills and temperamental traits also will contribute to the part of kindergarten culture that involves joint recognition of classroom rules (Lash 2008). Children create strategies for building their social unit based on mutual understanding of the limits set by the teacher.…”
Section: Children's Temperament and Peer Relationshipsmentioning
confidence: 99%
“…This view supports peer culture and peer learning. As shown by previous studies, when children sit in a classroom with their peers, discuss in groups, make jokes with each other and compete, they can both construct their knowledge and form a stronger identity (Lash, 2008;Hatch, 1989).…”
Section: Sociocultural Viewmentioning
confidence: 80%
“…Higher education has the second most usage of constructivism in the classroom. There are not many articles especially about constructivism in the kindergarten, however, it is highly recommended as social interaction has great importance in terms of "peer culture" which occurs when the little learner build and share information through activities in the created learning environment by the teacher (Lash, 2008). 3.3. How can constructivist approach be applied in multidisciplinary learning environments?…”
Section: 1mentioning
confidence: 99%